The effectiveness of "Soft-blocking" for reducing clicking on-screen while driving. (August 2021) - Shelef, Amit; Musicant, Oren; Botzer, Assaf; Mama, Yaniv
Highlights: Effectiveness of soft-blocking for reducing smartphone screen clicking while driving. Reduced clicking at speed thresholds (STs) 56 - 90 km/h during soft-blocking period. For STs 0 - 55 km/h during soft-blocking period, our analysis yielded mixed results. Abstract: Smartphone usage while driving is recognized as a compromise on road safety. We investigated if silencing and hiding of notifications from drivers (soft blocking) can reduce clicks on the screen while driving and if the effect of the soft blocking would be different for different speed thresholds (STs) (i.e., at driving speed greater than 0 km/h, greater than 1 km/h….and greater than 90 km/h). Drivers installed a smartphone application, which continuously monitored their phones. In the intervention group (N = 22), the application switched to the soft blocking mode during the study's intervention period, while in the control group (N = 29) it remained in a recording-only mode. We ran a Poisson regression model on the click events frequency (CEF) to estimate the soft blocking effect for each of the STs between 0 and 90 km/h. Our analyses indicated that the soft blocking effectiveness was indeed speed-dependent and pointed to a decline in CEF from ST > 55 km/h and to mixed results if ST < 55 km/h. We identify a potential of soft blocking to reduce phone usage while driving and recommend ST-dependent soft blocking. We also recommend using different STs in future investigations on the effectiveness of soft blocking.